Maintained functional diversity in benthic communities in spite of diverging functional identities. Issue 10 (22nd February 2016) - Weigel, Benjamin; Blenckner, Thorsten; Bonsdorff, Erik
Abstract : Ecological studies based on time‐series often investigate community changes centered on species abundance or biomass but rarely expose the consequential functional aspects underlying such changes. Functional diversity measures have proven to be more accurate predictors for ecosystem functioning than traditional taxonomic approaches and hence gained much attention. There are only limited studies available that analyse the functional implications behind decadal changes of entire communities. We studied zoobenthic communities of two habitats, sheltered and exposed, of a coastal system subject to contrasting changes in community composition over the past four decades. Besides eutrophication and climate‐related impacts, the system has been invaded by a non‐native polycheate Marenzelleria spp., adding altered functional properties to the communities. The functional dispersion (FDis) metric was used as a measure for comparing the functional diversity of the contrasting habitats, with special focus on the role of Marenzelleria for the entire communities. We highlight changes in the functional identity of the communities, expressed as community‐weighted means of trait expression (CWM), using multivariate techniques, and investigate the relationship between taxonomic and functional changes. Despite contrasting community developments in the two habitats, with characteristics traditionally suggesting different environmental quality, we found that the FDis in both habitats remained similar and increased with the introduction of Marenzelleria . Although showing maintained functional diversity across time and space, the functional identity (CWM) of communities changed irrespective of taxonomical differences. Examples include inter alia alterations in palatability proxies, feeding position and sediment transportation types, indicating changed functionality of zoobenthos in coastal systems. We show, when focussing on qualitative functional changes of communities, it is important to evaluate the underlying functional identity, and not only rely on measures of the diversity of functions per se, as the quality indication of expressed functional traits can be concealed when using multi‐functionality approaches.